Інвентаризація як метод бухгалтерського обліку - Букало, Надія Артемівна; Bukalo, Nadiia A.; Новицька, Ю. В.; Novytska, Yu. V. (Луцький національний технічний університет, 2015)
У статті наведено визначення поняття "інвентаризація" та розглянуто його тлумачення різними вітчизняними і зарубіжними науковцями. Визначено роль інвентаризації в господарській діяльності. Звернено увагу на основні етапи проведення інвентаризації. Досліджено бачення різних авторів щодо принципів проведення інвентаризації. The interpretation of the concept “inventory” and the visions of different Ukrainian and foreign scientists of it are given in the article. It is investigated, that inventory is an audit and documentary verification of an existence and a condition, an evaluation of assets and liabilities (property, investment of an enterprise in a statutory fund of other enterprises, settlements with debtors and creditors) of an enterprise. Inventory management is primarily about specifying the size and placement of stocked goods. Inventory management is required at different locations within a facility or within multiple locations of a supply network to protect the regular and planned course of production against the random disturbance of running out of materials or goods. The scope of inventory management also concerns the fine lines between replenishment lead time, carrying costs of inventory, asset management, inventory forecasting, inventory valuation, inventory visibility, future inventory price forecasting, physical inventory, available physical space for inventory, quality management, replenishment, returns and defective goods and demand forecasting and also by replenishment Or can be defined as the left out stock of any item used in an organization. The role of inventory in economic activity is examined. The attention is paid to the stages of carrying out an inventory. The visions of different authors concerning principles of carrying out an inventory are investigated. The ‘principle’ means the established, generally acknowledged and the most spread rules of economic actions and the qualities of economic processes. Specifically, continuity, documenting, economy, comparability of the measurement units, liability, actual presence of control units, promptness suddenness, comprehensiveness, timeliness, fidelity, objectivity, obligatoriness, and evaluation of results are the principles of carrying out an inventory. As an accounting and auditorial method, inventory provides a compliance of such reporting principles as authenticity and intelligibility, obtaining full and objective information about the presence, the condition of assets and liabilities.
Inventory as a method of accounting
Keywords: інвентаризація; запаси,; активи,; фінансова звітність,; облік,; stocks,; assets,; financial reporting,; accounting